Problems Of Translating Islamic Religious Terms Among Iraqi Students - Salah Habeeb, Luwaytha; Rasheed Muhammed, Muhammed (Opción, 2019)
This study concerns with analyzing the Iraqi students’ translation of some selected religious texts in regards to the fact that they are learners of English as a foreign language. The study is qualitative in nature and is done randomly. That is, a ques- tionnaire of fifteen Arabic religious terms are randomly chosen and are offered to fourteen college students (of AL- Anbar) who are randomly selected from the third and fourth years. It aims to answer the following questions 1) To what extent the students have the ability of translating Islamic terms from Arabic into English? 2) What are the solutions needed to improve students’ ability of translating Islamic terms from Arabic into English? The study adopts Liao’s (2010) model of classifi- cation of translation errors, in order to achieve the aims of the study. Based on the analysis of the data, the study finds out that, although most of the students managed to translate the required terms, errors are found. Two types of errors were found: rendition errors and language errors. They are related to misinterpretation of the source text and unawareness of its Islamic terms and also their poor syntax and se- mantics knowledge of English in addition to other reasons like there is no separate course for translation especially of religious texts or its limited number per week. Therefore, on the basis of these findings, some suggestions are put forward at the end of this study in order to develop students’ proficiency of translation.